(untitled) (Journal of history-rus, 2024)
The purpose of the article is to consider and analyze the main aspects of the Soviet state policy towards the Islamic religion and believers in 1917-1953 based on materials from the Aktobe region. The article examines some issues of the Soviet government policy towards Islam in the Aktobe region. Since 1929, merciless persecution of all confessions in the Soviet Union began. During this period, mosques were closed and church valuables were confiscated by decrees and orders from above. The state archive of the Aktobe region contains minutes and excerpts from meetings devoted to this issue. One of the organizations engaged in anti-religious propaganda is the Union of Militant Atheists. This organization was founded in 1925, branches were created in all regions, including the Aktobe region. In the course of preparing the article, were used documents from the Central state archive of the Republic of Kazakhstan (Almaty) and the state archive of the Aktobe region. To ensure objectivity in working on sources, the author conducted a comparative analysis of documents and materials from other regions of Kazakhstan, which also carried out this policy concerning a religious nature. In this case, the author used the following methods: specific analysis, comparative historical, problem-chronological and statistical. Using the comparative-historical method, we identified the objective relationship between historical facts and events occurring in the USSR and in the Aktobe region, and also compared events occurring in different territories of Soviet Kazakhstan. The scientific novelty of the study lies in the experience of studying the relationship between the Soviet state and religious organizations in 1917-1953 using the example of the Aktobe region. Based on extensive data from archival sources and monographs, as well as materials from the state commission for the full justification of victims of political persecution in the Aktobe region in the 20-50s of the twentieth century, it is substantiated that Soviet policy was carried out very deeply and systematically on the territory of the Aktobe region due to its border proximity. Кеу words: Islam, repression, OGPU, tactics of “religious tolerance”, anti-religious propaganda, Union of Atheists.